Drug Safety in Dentistry: Risk Factors, Non-Allergic Adverse Reactions, Pharmacovigilance, and Practical Recommendations - Lykhota Костянтин; Zaychenko Ганна; Grynevych Олександр; Simonova Оксана; Slobodyanik-Kolomoiets Мар’яна; Shmatko Володимир (Actual Dentistry, 2026)
This article systematizes current concepts of drug safety in dentistry. It reviews the most common adverse reactions, the main groups of drugs, risk factors for their occurrence, clinical examples, and statistical data from international and national sources. The experience of Ukraine in the field of dental pharmacovigilance is highlighted. Practical recommendations are proposed to help dentists minimize the risk of adverse reactions and improve the safety of pharmacotherapy. Purpose: to summarize contemporary scientific data on drug safety in dentistry, identify the main risk factors for adverse reactions, outline the principles of pharmacovigilance, and formulate practical recommendations for dental practitioners. Materials and methods: scientific literature (PubMed, Scopus, Google Scholar), statistics from EudraVigilance, VigiBase, and the State Expert Center of the Ministry of Health of Ukraine were analyzed. Practical recommendations were developed to reduce the risk of adverse reactions.